Development of A Scheduling System for RRI Cirebon Public Broadcasting - Adi Nugraha; Ahmad Zuhdi; Agus Salim (Intelmatics, 2021)
Abstract- LPP RRI Cirebon in making scheduling is currently not effective and efficient. In addition, broadcast administration still uses general computerization. Thus, for broadcast scheduling, the same broadcast schedule often occurs at one time and causes scheduling data loss. This final project will apply the software development cycle (SDLC) technique in building applications using the prototype method. The results of this final project can help the process of schedule patterns carried out by the broadcast administration of LPP RRI Cirebon to be effective and efficient. Then the purpose of this final project is also expected to facilitate scheduling making.Index terms-  scheduling, broadcast schedule, radio, RRI Cirebon